2020
DOI: 10.1108/ijis-04-2020-0046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of R&D intensity on the innovative performance of manufacturing companies. Evidence from Ecuador, Peru and Chile

Abstract: Purpose This paper aims to examine the relationship between research and development (R&D) intensity and innovative performance and R&D intensity as a moderating variable in the relationship between sources of information and innovative performance. Design/methodology/approach This is a quantitative, nonexperimental, cross-sectional study of the data collected from national surveys of innovation activities from Ecuador, Peru and Chile where the investigation was carried out. A bivariate probit regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…New technological knowledge allows a company to think about innovating its processes and operating habits, thereby recognizing new opportunities for innovation. Recent research conducted by Carvache-Franco, et al [19] provides new insights into the relationship between research and development (R&D) intensity and product and process innovation. The study found a positive association between R&D intensity and innovation in both products and processes in Ecuador and Peru.…”
Section: The Linkage Between Randd Intensity and Product Innovationmentioning
confidence: 99%
“…New technological knowledge allows a company to think about innovating its processes and operating habits, thereby recognizing new opportunities for innovation. Recent research conducted by Carvache-Franco, et al [19] provides new insights into the relationship between research and development (R&D) intensity and product and process innovation. The study found a positive association between R&D intensity and innovation in both products and processes in Ecuador and Peru.…”
Section: The Linkage Between Randd Intensity and Product Innovationmentioning
confidence: 99%
“…Thus, López-Mendoza & Mauricio (2020) analyzed how universities seek to interact with firms to carry out technology transfer projects, allowing them to improve the satisfaction of the firm's customers, by receiving better products. While Carvache-Franco et al (2020), analyzing Peruvian firms, found a contradictory result, that is, firms that interact with their consultants are less likely to develop product innovations.…”
Section: The Relationship Between Institutional Network and Product I...mentioning
confidence: 99%
“…With regard to Peruvian firms, it is important to point out that universities are generators of technological knowledge that helps firms develop innovations (Arenas & González, 2019). While Carvache-Franco et al (2020) analyzing Peruvian firms found a contradictory result, that is, firms that interact with their consultants are less likely to develop process innovations.…”
Section: The Relationship Between Institutional Network and Process I...mentioning
confidence: 99%
“…A good number of literature suggests that R&D intensity is another important indicator for firms' innovation activities (see Roper and Hewitt-Dundas, 2015;Carvache-Franco et al, 2020;Zhu et al, 2021). Taking this into account, knowledge intensive firms invest a relatively high proportion of revenues into R&D. As a result, firms' knowledge competencies increase in response to such kind of investment.…”
Section: Introductionmentioning
confidence: 99%
“…A good number of literature suggests that R&D intensity is another important indicator for firms' innovation activities (see Roper and Hewitt-Dundas, 2015; Carvache-Franco et al. , 2020; Zhu et al.…”
Section: Introductionmentioning
confidence: 99%